CONCEPTUAL STUDY ON MANAGEMENT OF RAKTARSHA - Gaudar, Shivaraj A; Kumar J, Santosh; John P, Elizabeth (Asian Journal of Pharmaceutical Research and Development, 2022)
In the present era Arsha has become most common and distressing disease due to Sedentary life style and irregular habits. Raktarshas is one of the bheda of ardraars has which is pittaraktanubandhi. The formation of mamsakura occurs which looks like vatankurasadrasha (Gunjaphalavata ,Vidrumasadrasha). Raktasrava, Shoola,Vibandha, Kandu and Daha are the characteristic features of Raktars has. Inmodern science Raktarshasiscor related with Bleeding Hemorrhoids. Chronic constipation is almost common cause of bleeding Hemorrhoids. Usually due to chronic constipation more pressure exerted on Hemorrhoidal veins as they have not contained any extra bony support hence it causes friction in the region which leads to varicosity of Hemorrhoidal veins which aa in due to chronic constipation yet strained and burst resulting in bleeding. Ayurvedic physician are treating this disease successfully with indigenous formulations and surgery.